Improving the quality of under water images with precision: Employing a CLAHE method - Chaitanya, Gogineni Krishna; Gaddam , Sasidhar Reddy; Ahmad , Khadri Syed Faizz; Vicharapu , Balaji; Soundharya , Uppuluri Lakshmi; Madhuri , Uppuluri Naga Lakshmi ‎ (International Journal of Basic and Applied Sciences, 2025)
This research paper undertakes a thorough and meticulous comparative exploration of diverse image enhancement techniques, focusing specifically on their application to underwater images and medical X-rays. Central to this investigation is the innovative Contrast Limited Adaptive Histogram Equalization (CLAHE) method, which stands in juxtaposition to the more conventional Adaptive Histogram Equalization (AHE) and Histogram Equalization (HE) techniques. The intrinsic challenges of underwater imaging and medical diagnostics, stemming from issues of diminished visibility and contrast, propel the urgency of this study. Herein, we introduce an inventive paradigm harnessing the CLAHE algorithm to efficaciously elevate image quality. The implementation of our proposed approach stands as a testament to its notable superiority over incumbent algorithms, as evidenced by substantial advancements in enhancement quality and computational efficiency.
Keywords: Image Processing; Image Enhancement; Histogram Equalization